2016
DOI: 10.1139/cjpp-2015-0277
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin synergistically enhances protective effect of atorvastatin against gentamicin-induced nephrotoxicity in rat kidney

Abstract: The risk of serious side-effects such as nephrotoxicity is the principal limitation of gentamicin (GEN) therapeutic efficacy. Oxidative stress is considered to be an important mediator of GEN-induced nephrotoxicity. The present study was designed to evaluate the efficacy of the combination of melatonin (MT) plus atorvastatin (ATO) against GEN-induced nephrotoxicity in rats. We utilized 30 male Wistar albino rats allocated in 5 groups, each containing 6 rats: control, GEN (100 mg/kg/day), ATO (10 mg/kg/day) + G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Furthermore, MEL ameliorates nephropathy in diabetic rats’ kidneys via attenuation of oxidative stress . Also, there are other studies about the protective effects of melatonin in nephrotoxicity induced by cyclosporine, adriamycin, lead, ochratoxin and gentamicin and our results are entirely consistent with these studies .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, MEL ameliorates nephropathy in diabetic rats’ kidneys via attenuation of oxidative stress . Also, there are other studies about the protective effects of melatonin in nephrotoxicity induced by cyclosporine, adriamycin, lead, ochratoxin and gentamicin and our results are entirely consistent with these studies .…”
Section: Discussionsupporting
confidence: 91%
“…In other studies on myocardial ischemia, atorvastatin exerts significant cardioprotective effects through increase of SOD and decreased MDA content (Sun et al, 2015). In the same direction, Mehrzadi et al (2016) stated that atorvastatin enhance the renal SOD activity however, not reduce MDA. Rats pretreated with atorvastatin 2 or 5 mg/kg/day challenged with acetaminophen, showed higher hepatic SOD activities, lower MDA levels (Farag et al, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Atorvastatin effectively reduced creatinine and may carry a good approach as potential antidiabetic effect and serve as the therapeutic drug for diabetic kidney disease management in streptozotocin-induced diabetic rats (Liao et al, 2016). On other hand, Mehrzadi et al (2016) mentioned that atorvastatin could not reduce elevated serum creatinine concentration, kidney weight, renal ROS and MDA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin can reduce hypoxia induced angiogenesis. It was found that the ability of MT to clear -OH is more than 5 times than that of glutathione (16,17). MT also has an indirect antioxidant effect, in that it can promote the expression of antioxidant defense enzymes by nuclear receptor mediated mechanisms, and enhance the activity of antioxidant enzymes (1820).…”
Section: Discussionmentioning
confidence: 99%